Optimizing the State Income through Law Enforcement and Law Supervision in the Field of Taxation - Dewi Mulyanti; Hendi Budiaman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Tax income is one of the state income resources that is used for development whose final purpose is for people’s welfare and prosperity. Tax income is a kind of a bigger state income compared to that generated from other kinds of income such as oil and gas income and non-oil and gas income. The success of a state in taxing its citizen will improve the stability of economy of the state. However, the state often finds it difficult to collect tax for many taxpayers who are obedient and dishonest and avoiding to pay taxes. This cause the government to create a mechanism to supervise and enforce law in the field of taxation. The attempt to optimizing the state earned income through tax paying plays an important role in the nation prosperity development.